ANALISIS PENGELOLAAN BARANG MILIK DAERAH BERDASARKAN PERMENDAGRI NOMOR 19 TAHUN 2016 (STUDI KASUS PADA DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI NTT) - Finch Dianan Pandu; R. Setyo Budi Suharto; Alfred T. Rantelobo (JAKA - Jurnal Jurusan Akuntasi, 2021)
The management of regional property at the Office of Archives and Libraries of the Province of NTT has not been carried out optimally so that the optimality in the management of regional property has not been achieved optimally. The problem studied in this study is how the management of regional property is carried out at the NTT Provincial Archives and Library Service whether it is in accordance with applicable regulations, and the purpose of this study is to determine the management of regional property based on Permendagri Number 19 of 2016 concerning guidelines for managing property. at the Department of Archives and Libraries of the Province of NTT. This study uses a qualitative descriptive data analysis technique, which aims to systematically describe and describe the facts of the object under study by comparing the results obtained between the regional property management system at the Archives and Library Office of NTT Province with Permendagri Number 19 of 2016. The results of this study indicate that overall it has been carried out properly and in accordance with the cycle of Regional Property Management as regulated in Permendagri Number 19 of 2016, although not all of them have been carried out optimally where the destruction stage is not carried out by the Archives and Library Office of NTT Province, and at the coaching stage has not been carried out by the Department of Archives and Libraries of the Province of NTT. So it can be concluded that the regional property management system at the Archives and Library Office of NTT Province is not fully in accordance with the regulation of the Minister of Home Affairs Number 19 of 2016